Comparative secretome analyses of primary murine white and brown adipocytes reveal novel adipokines - Ali Khan, Asrar; Hansson, Jenny; Weber, Peter; Föhr, Sophia; Krijgsveld, Jeroen; Herzig, Stephan; Scheideler, Marcel (Molecular & cellular proteomics, 2018)
Graphical Abstract - Download figureOpen in new tabDownload powerpoint - - Highlights - - First comparative proteomic analysis of white and brown adipocyte secretomes.100 novel adipokines differentially secreted from white versus brown adipocytes.Functionally enriched protein class changes in white and brown adipocytes.200 novel, NE-responsive adipokines from brown adipocytes. - The adipose organ, including white and brown adipose tissues, is an important player in systemic energy homeostasis, storing excess energy in form of lipids while releasing energy upon various energy demands. Recent studies have demonstrated that white and brown adipocytes also function as endocrine cells and regulate systemic metabolism by secreting factors that act locally and systemically. However, a comparative proteomic analysis of secreted factors from white and brown adipocytes and their responsiveness to adrenergic stimulation has not been reported yet. Therefore, we studied and compared the secretome of white and brown adipocytes, with and without norepinephrine (NE) stimulation. Our results reveal that carbohydrate-metabolism-regulating proteins are preferably secreted from white adipocytes, while brown adipocytes predominantly secrete a large variety of proteins. Upon NE stimulation, an increased secretion of known adipokines is favored by white adipocytes while brown adipocytes secreted higher amounts of novel adipokines. Furthermore, the secretory response between NE-stimulated and basal state was multifaceted addressing lipid and glucose metabolism, adipogenesis, and antioxidative reactions. Intriguingly, NE stimulation drastically changed the secretome in brown adipocytes. In conclusion, our study provides a comprehensive catalogue of novel adipokine candidates secreted from white and brown adipocytes with many of them responsive to NE. Given the beneficial effects of brown adipose tissue activation on its endocrine function and systemic metabolism, this study provides an archive of novel batokine candidates and biomarkers for activated brown adipose tissue.